2022
DOI: 10.1021/acscatal.2c03849
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Nanostructures Promoting Electrocatalytic Reactions with Three-Dimensional Frameworks

Abstract: Hollow skeletal nanomaterials, such as nanoframes and nanocages, represent a class of advanced electrocatalysts and exhibit excellent performance in various electrochemical energy conversion reactions. Their three-dimensional (3D) framework, which allows a high surface-area-to-volume ratio, efficient molecular accessibility, and nanoscale confinement effect, leads to higher catalytic activity compared to solid nanoparticle (NP)-based catalysts without requiring the use of a significant amount of precious metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…To investigate the electrocatalytic activity of our printed material with high porosity, the printed FePt porous material was chosen for the oxygen reduction reaction (ORR) because the FePt nanostructures are renowned as highly active catalysts with a suitable binding energy between their surfaces and the ORR intermediate (Supplementary Fig. 26 ) 52 . To afford clean surfaces for promoting the catalytic activity, we removed the metal ion linker and surface ligands in printed materials via acid treatment in 0.1 M HCl solution and subsequent electrochemical cycling activation in 1.0–1.5 V (vs. RHE) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the electrocatalytic activity of our printed material with high porosity, the printed FePt porous material was chosen for the oxygen reduction reaction (ORR) because the FePt nanostructures are renowned as highly active catalysts with a suitable binding energy between their surfaces and the ORR intermediate (Supplementary Fig. 26 ) 52 . To afford clean surfaces for promoting the catalytic activity, we removed the metal ion linker and surface ligands in printed materials via acid treatment in 0.1 M HCl solution and subsequent electrochemical cycling activation in 1.0–1.5 V (vs. RHE) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that this enhancement could be driven by a significant increase in the electric conductivity. The three-dimensional (3D) structures comprising multimetallic components, such as core–shell, nanoframes, and other morphologies, have also demonstrated excellence as OER catalysts. Oh et al proposed a hollow, rattle-like Pt/NiO/RuO 2 catalyst comprising a Pt/Ni-doped RuO 2 icosahedral framework as an excellent catalyst for the acidic OER.…”
Section: Design Strategies For Improving Catalytic Performancementioning
confidence: 99%
“…In particular, the NT morphology ensured additional increases in surface area and defective surfaces due to internal voids. Furthermore, the internal voids can allow extraordinary enhancement of catalytic reactivity via the nanoscale confinement effect, frequently observed in three-dimensional skeletal nanoarchitectures, leading to strides in antioxidation efficacy [30][31][32].…”
Section: Physicochemical Properties Of Ceria Antioxidantsmentioning
confidence: 99%